Measuring pressure interface of local car seats under static and dynamic circumstances: a comparative study - Khamis, N.K; Roslan, A.F; Deros, B.M; Ismail, A.R (2018)
Measuring discomfort towardthe car seat is important as the act of driving requires a driver to remain at the car seat while controlling the car. The seat condition, including sitting position as well as the driver’s posture can lead to discomfort and fatigue. The objective of this study is to investigate a driver’s pressure distribution in static and dynamic circumstances for two types of cars; the sedan and compact car. This study involved both subjective and objective evaluations of 12 respondents. For the subjective evaluation, the Visual Analog Scales (VAS) were used to obtain respondents' perception of discomfort. For the objective evaluation, pressure distribution readings of the seat interface were obtained using piezo capacitive sensors. The findings showed that the highest pressure was recorded for the compact car. Furthermore, the static circumstance showed greater pressure compared to the dynamic state. Subjective evaluation indicated that the right buttocks and the lower back (lumbar)experience the highest discomfort for both types of seats.The type of seat found to contribute to the value of different pressure. Thus, it can be concluded that appropriate seat selection can reduce pressure as well as discomfort.